IMPLEMENTASI PEMENUHAN HAK-HAK KORBAN PEREMPUAN YANG BERPROFESI SEBAGAI PEKERJA RUMAH TANGGA DALAM UPAYA PENCEGAHAN TERHADAP BENTUK KEKERASAN DALAM RUMAH TANGGA - Tian Terina (KEADILAN PROGRESIF, 2019)
Violence is basically a form of crime. Responding to the violence that occurred at thistime was not spared from observations namely about violence that occurred in the household.It is possible that violence can occur to domestic workers because domestic workers areincluded in the scope of the household. The problem in this research is how to implement thefulfillment of the rights of women victims who work as domestic workers in an effort toprevent forms of domestic violence and what forms of legal protection for women who workas domestic workers? This study uses a Normative and Empirical Juridical approach. Theresults showed that the implementation of fulfilling the rights of women victims who workedas domestic workers in an effort to prevent other forms of domestic violence in real steps bythe government and the state was realized through pre-emptive efforts, namely issuingseveral regulations and promoting forms of fulfilling rights . victims in their capacity asdomestic servants. A form of legal protection for women who work as domestic workers.First, the legal protection provided to domestic workers can be divided into two parts,namely: First, formal criminal law protection for domestic workers who have been victims ofcrime, this protection is to obtain legal guarantees or compensation for the suffering or lossof someone who has become a victim of crime, including the right of the victim to obtain thefulfillment of rights. Second, the protection provided in material criminal law is in the form ofprotection to fulfill the rights of those who are victims of violence and their forms andfacilities. Suggestions conveyed by the authors in this study an effort to create a decent worksituation for domestic workers needs to be done. by passing the Domestic Workers ProtectionBill. Endorsement efforts must always be encouraged. This is because it is very important fordomestic workers to be recognized as workers.